The Mental Stress Ischemia Prognosis Study: Objectives, Study Design, and Prevalence of Inducible Ischemia. Issue 3 (April 2017) - Hammadah, Muhammad; Al Mheid, Ibhar; Wilmot, Kobina; Ramadan, Ronnie; Shah, Amit J.; Sun, Yan; Pearce, Brad; Garcia, Ernest V.; Kutner, Michael; Bremner, J. Douglas; Esteves, Fabio; Raggi, Paolo; et al.
ABSTRACT: Objective: Mental stress–induced myocardial ischemia (MSIMI) is a common phenomenon in patients with coronary artery disease (CAD), but contemporary studies of its prognostic significance and its underlying pathophysiology are limited. Methods: We prospectively enrolled patients with confirmed CAD in the Mental Stress Ischemia Prognosis Study (MIPS) between 2011 and 2014. All patients underwent mental stress testing using a standardized public speaking task, and ischemia was detected by 99m Tc-sestamibi myocardial perfusion imaging. Patients also underwent conventional stress testing for myocardial ischemia (CSIMI) using exercise or pharmacological stress testing. Furthermore, digital microvascular flow, endothelial function, arterial stiffness, and blood sample collections were performed before, during, and after mental stress. Two-year adverse clinical outcomes are being assessed. Results: Six-hundred ninety-five patients completed baseline enrollment in the MIPS. Their mean (standard deviation) age was 62.9 (9.1) years, 72% were men, 30% were African American, and 32% had a history myocardial infarction. The prevalence of MSIMI and CSIMI is 16.1% and 34.7%, respectively. A total of 151 patients (22.9%) had only CSIMI, 28 (4.2%) had only MSIMI, and 78 (11.8%) had both MSIMI and CSIMI. Patients with ischemia had a lower ejection fraction and higher prevalence of previous coronary artery bypass grafting compared with those without inducible ischemia ( p < .050). The prevalence of obstructive CAD was not statistically different between patients with and without MSIMI ( p = .426); in contrast, it was higher in patients with CSIMI ( p < .001). Conclusions: The MIPS data will provide useful information to assess the prognostic significance and underlying mechanisms of MSIMI.